PROGRAM REGENERASI TERHADAP DEGRADASI BUDAYA CINA BENTENG DI KOTA TANGERANG - Ronaldo, Ronaldo; Jayanti, Theresia Budi (Jurusan Arsitektur dan Perencanaan, 2024)
Cina Benteng are ethnic Chinese who dominate the Tangerang area. Regeneration activities in improving the quality of cultural elements to deal with the problem of cultural degradation have become the focal point for architectural program development. The problem of cultural degradation from modernization factors increasingly makes the value of a culture less visible and diminished by developments over time. The regeneration program is a development that maintains cultural heritage, traditions, and activities passed down from generation to generation, becoming a combination of programs in one complete space. Program conditions that have been supported by the surrounding social context which has been well acculturated support the program. With the regeneration program, it is hoped that it can become an important reference as a form of returning the memories that form the active interaction patterns of Cina Benteng, in order to maintain traditions passed down from generation to generation. The method of this research uses qualitative methods, through direct observation of existing buildings that have become icons for preserving the Cina Benteng cultural heritage. Analysis from Cina Benteng people in maintaining traditions becomes a reference for selected